Membaca Ulang Diskursus Perang dalam al-Qur’an Perspektif Muhammad Abdel Haleem - Taufik Akbar (IAIN Bengkulu, 2022)
This article aims to to explore Abdel Haleem's perspective on the portrayal of war in the Koran. The concept of war in the Quran has long been associated with negative connotations against Islam. However, Haleem offers a distinct perspective to help comprehend the concept of war in the Quran. Using a qualitative research design employing a character criticism research model, this article reveals that the conventional understanding of the concept of war has undergone several distortions, as both Muslim and Western scholars have misconstrued it. Haleem attributes these errors to misunderstandings of the Islamic terminology used for war, particularly the translation of the terms qital and jihad. The Quran commands war only to establish justice and peace. Although the theme of war in the Quran cannot be used without clear objectives, Haleem acknowledges the importance of the concept of war as a means to halt crime.